METODE LUDO DAN TEBAK GAMBAR TERHADAP PENGETAHUAN REMAJA TENTANG HIV/AIDS - Flora Niu; Sri Wahyuni; Marlisa Prismadini (JKM (Jurnal Kebidanan Malahayati), 2021)
THE LUDO METHOD AND GUESS THE PICTURE ON ADOLESCENT KNOWLEDGE ABOUT HIV/AIDS  Background : according to the health profil of jayapura district, there are 2.973 cases of HIV/AIDS as of december 2018 cumulatively, there are 2.973 cases of HIV and AIDS 1.576 cases, 346 deaths, 275 AIDS cases, the highest number of HIV/AIDS attacks at productive age (15-29 years) as many as 2.752 cases. Purpose : to determine the comparison of the ludo methode and gues the picture to the knowledge of adolescents about HIV/AIDS in Nimbokrag VillageMethods : comparative research. This research was carried out in nimbokrang villagein july 2020. The population in this study were 136 adolescents in nimbokrang, a sample of 30 respondents, this sample was taken by random smpling. The instruments used were the image guessing game questionnaire and the lludo game. This questionnaire has been tested for validity and reliability, data analysis techniques with bivariate analysis. Result : based on the research of the pre-test and post-test of both methods, the pre-test and post-trst result of the ludo method have a p value of 0,000 < 0,05, so there is a difference between the knowledge of pre-test and post-test in the ludo methode, on the pre-test and post-test. The image guessing method result in the p value is 0,000 < 0,05, so there is a defference between the pre test and post testin the image guessing method. If seen from the result of the effectiveness teat, the p value is 0,175 > 0,05, so there is no difference between the ludo method and guess the piture, which means that they are equally effective in increasing adolescent knowledge about HIV/AIDS. Conclusion : from the both methods are result of the two methods above, it can be concluded that both methods are qually effective in increasing adolescent knowledge about HIV/AIDS.Suggestion adolescents increase their knowledge in seeking information about HIV / AIDS by following counseling conducted by health workers and from various media, both print and electronic media Keywords : knowledge, adolescent, HIV/AIDS, Ludo, Guess the picture.  ABSTRAK Latar belakang : Menurut Profil Kesehatan Kabupaten Jayapura, (2018) kasus HIV/AIDS  sampai dengan Desember 2018 secara komulatif sebanyak 2973 kasus HIV 1397 dan AIDS 1576 kasus, meninggal 346, kasus AIDS yang meninggaal berjumlah 275 orang, angka tertinggi HIV/AIDS menyerang pada usia produktif (15-29 tahun) sebanyak 2751 kasus.Tujuan : Untuk mengetahui perbandingan Metode Ludo dan Tebak Gambar terhadap pengetahuan remaja tentang HIV/AIDS di Kampung NimbokrangMetode : Penelitian komperatif. Penelitian ini dilakukan di Kampung Nimbokrang pada bulan juli 2020. Populasi dalam penelitian ini adalah remaja dinimbokrang yang berjumlah 136 orang, dan sampel 30 responden, pengambilan sampel ini dilakukan dengan Sample Random Sampling. Instrumen yang digunakan adalah kuisioner permmainan tebak gambar dan permainan ludo. Kuisioner ini telah di uji validitas dan reliabilitasnya, teknik analisis data dengan analisis bivariat.Hasil : Berdasarkan hasil penelitian pre test dan post test kedua metode tersebut didapatkan hasil pre test dan post test metode ludo p valuenya 0,000 < 0,05 maka terdapat perbedaan antara pengetahuan pre test dan post test pada metode ludo, pada pre test dan post test metode tebak gambar didapatkan hasil nilai p valuenya 0,000 < 0,05 maka terdapat perbedaan antara pengetahuan pre test dan post test pada metode tebak gambar. Jika dilihat dari hasil uji efektiivitas didapatkan hasil nilai p valuenya adalah 0,175 > 0,05 maka, tidak terdapat perbedaan antara metode ludo dan tebak gambar, yang artinya sama-sama efektif digunakan dalam meningkatkan pengetahuan remaja tentang HIV/AIDS. Simpulan : dilihat dari hasil kedua metode diatas dapat disimpulkan jika kedua metode sama-sama efektif digunakan untuk meningkatkan pengetahuan remaja tentang HIV/AIDS.Saran para remaja meningkatkan pengetahuan dalam mencari informasi tentang HIV/AIDS dengan mengikuti penyuluhan yang dilakukan oleh tenaga kesehatan dan dari berbagai media baik media cetak maupun media elektronik Kata Kunci : Pengetahuan, remaja, HIV/AIDS, Ludo, Tebak Gambar.